Placental Transfer of Fc‐Containing Biopharmaceuticals across Species, an Industry Survey Analysis. (3rd January 2014) - Bowman, Christopher J.; Breslin, William J.; Connor, Anu V.; Martin, Pauline L.; Moffat, Graeme J.; Sivaraman, Lakshmi; Tornesi, M. Belen; Chivers, Simon
<x xml:space="preserve">Abstract</x> BACKGROUND Understanding species differences in placental transfer of Fc‐containing biopharmaceuticals (particularly monoclonal antibodies) will improve human risk extrapolation from nonclinical embryo‐fetal development toxicity data. METHODS Maternal and fetal concentration data from 10, 15, 8, and 34 Fc‐containing biopharmaceuticals in the rabbit, rat, mouse, and cynomolgus monkey, respectively, from an industry survey were analyzed for trends in placental transfer. RESULTS AND CONCLUSIONS Embryonic (before the end of organogenesis) exposure was assessed in one molecule each in rabbit, rat, and mouse, but detectable levels were present only in rodents. In rodents, fetal levels remained relatively constant from gestation day (GD) 16 and 17 until the end of gestation, while maternal levels decreased or remained constant in rat and decreased in mice. In rabbits, following a last dose on GD 19, fetal levels increased markedly in late gestation while maternal levels decreased. In the cynomolgus monkey, fetal levels increased substantially from GD 50 to 100 and were maintained relatively constant through parturition (approximately GD 165). Based on available data of both the monkey and rabbit, IgG1 molecules appeared to transfer more readily than other isotypes in late gestation. Across all species, there was no differential transfer based on pharmacologic target being soluble or membrane bound. Within each species there was a correlation between maternal and fetal exposure, suggesting it may be possible to predict fetal exposures from maternal exposure data. These nonclinical data (both temporal and quantitative aspects) are discussed in a comparative context relative to our understanding of IgG placental transfer in humans.